Risk Factors and Long-Term Prognosis for Chylothorax After Total Cavopulmonary Connection in Children: A Retrospective Study From a Single Center - Bai, Liting; Feng, Zhengyi; Zhao, Ju; Guo, Shengwen; Tong, Yuanyuan; Jin, Yu; Zhang, Peiyao; Gao, Peng; Li, Yixuan; Liu, Jinping (Frontiers in Pediatrics, 2021)
Background: Chylothorax is a severe complication after total cavopulmonary connection (TCPC) in children. This study was performed to evaluate the incidence, risk factors, short- and long-term prognosis for chylothorax. Methods: We retrospectively reviewed the electric records of patients who underwent TCPC between January 2008 and December 2020 in Fuwai Hospital. Patients were divided into two groups based on the occurrence of postoperative chylothorax. Univariate and multivariate analyses were performed to identify risk factors, and long-term survival was estimated by the Kaplan-Meier method. Results: Of 386 patients included in our study, chylothorax occurred in 60 (15.5%) patients. Compared with the non-chylothorax group, the prevalence of prolonged ICU (p=0.000) and postoperative hospital stay (p=0.000) were greater in patients with chylothorax. Postoperative adverse events in terms of infection (p=0.002), ascites (p=0.001), prolonged pleural effusion (p=0.000), and diaphragmatic paralysis (p=0.026) were more frequent in chylothorax patients. The median follow-up duration was 4.0 (2.0, 6.8) years. The chylothorax group had significantly lower survival rates at 1-year (92.4% vs. 99.3%, p<0.001) and 10-year (84.6% vs. 91.6%, p<0.001) respectively. Having a right dominant ventricle (OR 2.711, 95%CI: 1.285-5.721, p=0.009) and a higher peak central venous pressure on postoperative day (POD) 0 (OR 1.116, 95%CI: 1.011-1.233, p=0.030) were the risk factors for the development of chylothorax after TCPC operation. Conclusion: The incidence of chylothorax in patients undergoing TCPC is lower than previously reported, but is associated with poor early- and long-term survival. Having a right dominant ventricle and a higher peak central venous pressure on POD 0 are the risk factors for chylothorax after TCPC operation.